Assessing stakeholder’s view for quality bus services in Kuala Lumpur - Norhisham, Shuhairy; Abu Bakar, Muhammad Fadhlullah; Tajri, Azri Ahmad; Mohamad, Daud; Yatuka, Sotaro; Masjuki, Siti Aliyyah (Science and Engineering Research Support Society, 2019)
Malaysia will be one the developed countries in the next 10 years. Major cities such as Klang Valley will receive big impact on this development. Population and vehicle will growth as same as development year by year in especially in Klang Valley. The increase of vehicle in this country has caused a major problem in Klang Valley. The government has provided certain initiative to resolve this issue by implementation of Bus Network Revamp (BNR) in 2015. There is no comprehensive studies has conducted to evaluate the quality of bus in West Kelang Valley previously. The objective of this initiative is to reorganize and rearrange the existing bus service in Klang Valley in order to improve their service quality. this study was aimed to determine the of stakeholder’s view on the bus performance in West Klang Valley. 500 questionnaires have been distributed in targeted area in West Klang Valley such as Puchong, Subang Jaya, Klang, Shah Alam and Petaling Jaya. Specific criteria have been selected in order to determine the quality of bus service in these studies. Based on the result showed that, the overall quality of bus service in Puhong, Klang and Petaling Jaya have Medium qualityof bus service meanwhile Shah Alam and Subang Jaya have Good quality of bus service. Subang Jaya routes has received highest number of “Very Good” feedback from respondent compared with other routes. These studies only covered five main cities in West Klang Valley. Therefore, furthers studies in these area should be covered all routes in Klang Valley, as to provide a better comparison between quality of service of bus and stakeholders’ views on bus performance in West Klang Valley. There is few problems should encounter regarding public transport issues in Klang Valley. As a public service provider, feedback from passenger is important and all weakness should be address in future.